The Joule-Thomson effect and the non-equilibrium thermodynamics of sliding nano-contact; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Deeva V. S. Vera Stepanovna (2021, 2021)
Title screen